Pengelolaan Limbah Rumah Sakit Oleh Dinas Lingkungan Hidup Daerah Sulawesi Selatan - Fediyatun Muntazarah; Heri Tahir; Muhammad Akbal (Phinisi Integration Review, 2020)
This study aims to describe (1) hospital waste management by the Regional Environmental Service in a socio juridical study reviewed through several legislation regarding environmental management, especially hospital waste; (2) barriers faced by the South Sulawesi Regional Environmental Service; (3) efforts conducted in handling obstacles; (4) legal arrangements regarding hospital waste management by the South Sulawesi Regional Environment Agency. This type of research is qualitative research with a phenomenological approach, where the type of research is carried out by observing the subjects and objects to be studied based on the facts that exist. The facts found are described in depth. Data collection techniques using observation, interviews, and documentation, and analyzed by triangulation techniques. The results of this study indicate that: (1) Hospital waste management by the South Sulawesi Regional Environmental Service has not proceeded as expected due to the lack of facilities in the management of medical waste, and the lack of guidance and supervision of hospitals that still deviate from established rules marked by the absence of hospitals that have passed the company performance rating assessment program in environmental management. (2) Obstacles faced in hospital waste management are the lack of facilities especially incinerators and supervision as well as guidance for hospitals related to hospital waste management. (3) Efforts made by adding facilities related to hospital waste management and providing guidance to hospitals in South Sulawesi (4) Legal arrangements referred to by the South Sulawesi Regional Environment Agency refer to the three main legislation used as guidelines and the legal basis in the implementation of waste management, namely the legislation governing environmental protection and management as well as the legislation governing the management of B3 waste.